2005
DOI: 10.1021/es049796i
|View full text |Cite
|
Sign up to set email alerts
|

Primary Measures for Reduction of PCDD/F in Co-Combustion of Lignite Coal and Waste:  Effect of Various Inhibitors

Abstract: Co-combustion of coal and waste in power plants poses both environmental and economic challenges, especially because of the high polychlorinated dibenzo-p-dioxin and furan (PCDD/F) emissions from solid waste. In this study, we performed a series of experiments focusing on the prevention of PCDD/F formation by the use of various inhibitors added to the fuel before combustion. A mixture of lignite coal, solid waste, and poly(vinyl chloride) (PVC) was thermally treated in a laboratory-scale furnace at 400 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 24 publications
(29 reference statements)
0
27
0
Order By: Relevance
“…This indicates that the inhibition mechanisms may be highly temperature dependent and likely different for PCDD and PCDF, respectively. It has been reported that the suppression effects of sulphur-containing compounds are higher for lower chlorinated PCDD and higher chlorinated PCDF (Pandelova et al, 2005;. In addition, Chang et al (2006) reported that PCDD/F inhibition in the particulate-phase was more than the gaseous-phase and PCDD was reduced more than PCDF.…”
Section: The [Pcdf]mentioning
confidence: 99%
“…This indicates that the inhibition mechanisms may be highly temperature dependent and likely different for PCDD and PCDF, respectively. It has been reported that the suppression effects of sulphur-containing compounds are higher for lower chlorinated PCDD and higher chlorinated PCDF (Pandelova et al, 2005;. In addition, Chang et al (2006) reported that PCDD/F inhibition in the particulate-phase was more than the gaseous-phase and PCDD was reduced more than PCDF.…”
Section: The [Pcdf]mentioning
confidence: 99%
“…Many sources for the emission of UP-POPs have been identified and quantified (7,8), and the effects of various parameters on the formation of UPPOPs have been demonstrated in many studies (9)(10)(11)(12)(13). Sources of POPs and their relative importance have changed substantially over the past several decades.…”
Section: Introductionmentioning
confidence: 99%
“…To the most frequently encountered inhibitors there belong nitrogen and sulphur compounds which bring about the blocking of the metallic active centers in the particles of volatile dust, on the surface of which one may notice "de novo" synthesis [50][51][52][53][54].…”
Section: Methods Of Dioxins Emission Reductionmentioning
confidence: 99%